Management of citrus canker in Argentina, a success story - Canteros, Blanca Isabel (2017)
Citrus canker is an important bacterial disease of citrus in several regions of the world. Strains of Xanthomonas citri type-A (Xc-A) group are the primary pathogen where citrus canker occurs. After Xc-A entered the Northeast of Argentina in 1974, the disease spread rapidly from 1977 to 1980 and then slowed down and remained moving at slow pace until 1990 when it became endemic. Citrus canker was detected in Northwest Argentina in 2002. This paper presents the main steps in the fight of the disease and the management strategies that have been used to control citrus canker at this time. We think the process might be usefull to other countries with the same situation. Results from more than 40 years of research in Northeast (NE) Argentina indicate that we are at the limit of favorable environment for the disease. The severity of citrus canker is greatly affected by the environment and El Niño Southern Oscillation (ENSO) phenomenon which causes cyclic fluctuations on the disease intensity in the NE region. Weather-based logistic regression models adjusted to quantify disease levels in field conditions showed that the environmental effect was strongly modulated by the distance from a windbreak. Production of healthy fruits in citrus canker endemic areas is possible knowing the dynamics of the disease. A voluntary Integrated Plan to Reduce the Risk of Canker has been in place since 1994 and it allows growers to export unsymptomatic, uninfested fresh fruit to countries which are free of the disease and require healthy, pathogen free fruits. The experience from Argentina can be replicated in other countries after appropriate trials.